1964
DOI: 10.6028/jres.068d.054
|View full text |Cite
|
Sign up to set email alerts
|

Radiation from an aperture in a coated plane

Abstract: In this paper the method developed by J. R. Wait to determine th e fi elds produced by an aperture in an infinite coated-metal cylinder is extended to obtain the s olution for the fields produced by an apert ure in an infinite coated-m etal plane. Although t he fi elds at any point can be found by this method, this paper treats only the radi rLt ion fi elds (a futur e paper is planned which will treat the near fields and input admittance of the aperture). It is shown that the ra diation fi elds produced by a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1964
1964
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The process of comparing measurement with theory was complicated by the fact that the majority of the tested samples were anisotropic, so models describing radiation from a rectangular waveguide aperture into an isotropic medium [42]- [44] could not be utilized. Thus, theoretical calculations of waveguide-flange cavity response presented in this section are based on calculations performed for that purpose, which are detailed in [44].…”
Section: Dielectric Characterizationmentioning
confidence: 99%
“…The process of comparing measurement with theory was complicated by the fact that the majority of the tested samples were anisotropic, so models describing radiation from a rectangular waveguide aperture into an isotropic medium [42]- [44] could not be utilized. Thus, theoretical calculations of waveguide-flange cavity response presented in this section are based on calculations performed for that purpose, which are detailed in [44].…”
Section: Dielectric Characterizationmentioning
confidence: 99%
“…k 0 b) 2 G sm2 7}: = (kob) (kod) k;b ·, which is small compared with the terms retained in (B6). Knop and Cohn (1964) have shown that if the shape of the aperture distribution is not changed by the plasma, the 0 and cf> components ( 0 is the polar angle, and cf> is the azimuthal angle, measured relative to the x axis) of the radiation fields can be written as Using the conditions of (1) for the impedance-sheet approximation (i.e., Er ~ L vl"i",.kod ~ 1), we can write for {! (0) andf(O)…”
Section: Appendix B Derivation Of (2) As a Limiting Case Of A Finitementioning
confidence: 99%
“…The solutioa can be formulated in a straightforward manner using Fourier transforms [Knop and Cohn, 1964] . One obtains…”
Section: 2 Rectangular Slot Antennamentioning
confidence: 99%